Dynamic bond graph modelling of a two-phase cooling system with experimental analysis. (22nd June 2021) - Kebdani, Mohamed; Dauphin-Tanguy, Geneviève
The power electronics components are a significant source of heat energy which must be managed in spite of conventional cooling systems' limitations. In order to surpass these restrictions, an innovative heat transfer system is here investigated: two-phase loop mechanically pump (TLMP). An instrumented test rig is built with temperature, pressure and mass flow rate sensors to analyse the flow response in both steady and transient state. In this work, we focus on the pump-pipes subsystem. The results confirm the system's ability to manage heat power dissipation by maintaining stable power electronics temperature. In addition, the experiment results validate a thermo-hydraulic model based on 'bond graph' theory. The variables used to simulate phase-change phenomena are: mass enthalpy, temperature and pressure. This modelling allows estimating the influence of external conditions on loop operation. Moreover, it offers sizing prospects for this kind of loop development on-board future missiles.